Komitmen Guru PAI Terhadap Pembinaan Akhlak Peserta Didik Pada Era Digital di SMP Negeri 1 Jebus - Dessy Susanti (4, 2026)
This study explores the commitment of Islamic Religious Education (PAI) teachers in nurturing students’ moral character in the digital era at SMP Negeri 1 Jebus, West Bangka Regency. The background of this research stems from the significant challenges faced by PAI teachers amid the rapid progress of digital technology, which has reshaped students’ behavior, ways of thinking, and moral orientation. Easy access to information through the internet and social media has had a considerable impact on students’ character formation and patterns of interaction within the school environment. The study aims to describe the forms of commitment demonstrated by PAI teachers in fostering students’ moral values in the digital era. A qualitative approach was employed using a case study method. Data were gathered through interviews, observations, and documentation involving the principal, PAI teachers, and students. Data analysis followed the Miles and Huberman interactive model. The results of this study indicate that: 1) The commitment of PAI teachers at SMP Negeri 1 Jebus is reflected in various dimensions, such as exemplary conduct, moral responsibility in shaping students’ character, and consistency in integrating Islamic values across the learning process. 2) The strategies employed by teachers include value-based learning, habituation programs such as congregational prayers, short sermons (kultum), and Islamic digital literacy activities, as well as the use of online platforms to share light Islamic messages that are relevant to students’ daily lives. 3) Supporting factors of teacher commitment consist of institutional support, adequate digital infrastructure, and strong collaborative relationships among teachers and parents. 4) Challenges encountered include insufficient supervision of students’ social media usage, limited Islamic digital literacy, and social environmental influences that are not always aligned with moral educational values. 5) Despite these obstacles, PAI teachers consistently strive to uphold their commitment by strengthening personal approaches, enhancing creativity in teaching, and engaging in ongoing reflection and innovation to ensure that moral education remains meaningful and adaptive in the digital age. Abstrak Penelitian ini mengkaji tentang komitmen guru Pendidikan Agama Islam (PAI) dalam membina akhlak siswa pada era digital di SMP Negeri 1 Jebus, Kabupaten Bangka Barat. Latar belakang penelitian ini adalah adanya tantangan besar bagi guru PAI di tengah pesatnya kemajuan teknologi digital yang telah mengubah perilaku, cara berpikir, dan nilai moral peserta didik. Kemudahan akses terhadap informasi melalui internet dan media sosial sering memengaruhi karakter serta pola interaksi siswa di lingkungan sekolah. Penelitian ini bertujuan untuk mendeskripsikan bentuk komitmen guru PAI dalam pembinaan akhlak siswa pada era digital. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara, observasi, dan dokumentasi terhadap kepala sekolah, guru PAI, dan peserta didik. Teknik analisis data menggunakan model Miles dan Huberman. Hasil penelitian ini menunjukkan bahwa: Bentuk komitmen guru PAI di SMP Negeri 1 Jebus tercermin dalam berbagai aspek, antara lain keteladanan dalam berperilaku, tanggung jawab moral terhadap pembinaan karakter siswa, hingga konsistensi dalam menerapkan nilai-nilai Islam. Strategi yang digunakan guru PAI dalam membina akhlak meliputi pembelajaran berbasis nilai (value-based learning), kegiatan pembiasaan seperti salat berjamaah, kultum, dan literasi digital Islami, serta penggunaan platform daring untuk menyebarkan materi dakwah ringan yang relevan dengan kehidupan sehari-hari siswa. Faktor pendukung komitmen guru PAI antara lain adanya dukungan, ketersediaan sarana dan prasarana digital yang memadai, serta kerja sama yang optimal. Faktor penghambat meliputi lemahnya pengawasan penggunaan media sosial oleh siswa, rendahnya literasi digital Islami, dan pengaruh lingkungan sosial yang tidak selalu sejalan dengan nilai-nilai pendidikan akhlak. Meskipun menghadapi kendala tersebut, guru PAI tetap berupaya meneguhkan komitmen mereka dengan memperkuat pendekatan personal, meningkatkan kreativitas dalam pembelajaran, serta terus melakukan refleksi dan inovasi agar pendidikan akhlak tetap relevan di era digital.